2020
DOI: 10.3390/nu12102972
|View full text |Cite
|
Sign up to set email alerts
|

The GReat-Child TrialTM: A Quasi-Experimental Dietary Intervention among Overweight and Obese Children

Abstract: Diet composition is a key determinant of childhood obesity. While whole grains and micronutrients are known to decrease the risk of obesity, there are no interventions originating from Southeast Asia that emphasize whole grain as a strategy to improve overall quality of diet in combating childhood obesity. The GReat-Child Trial aimed to improve whole grain intake and quality of diet among overweight and obese children. It is a quasi-experimental intervention based on Social Cognitive Theory. It has a 12-week i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…The facilitator of repeated exposure to similar tastes may be included in the nutrition intervention, in which Malaysians are offered the same whole-grain food repeatedly and consistently over a long time. This facilitator is effective in increasing the whole-grain intake in a total of 31 Malaysian schoolchildren, carried out through an intervention named GReat-Child Trial™ (Koo et al, 2020). Perhaps, Improve whole-grain consumption the Malaysian government or non-government organisations may adopt the GReat-Child Trial™ intervention and implement it nationwide.…”
Section: Discussionmentioning
confidence: 99%
“…The facilitator of repeated exposure to similar tastes may be included in the nutrition intervention, in which Malaysians are offered the same whole-grain food repeatedly and consistently over a long time. This facilitator is effective in increasing the whole-grain intake in a total of 31 Malaysian schoolchildren, carried out through an intervention named GReat-Child Trial™ (Koo et al, 2020). Perhaps, Improve whole-grain consumption the Malaysian government or non-government organisations may adopt the GReat-Child Trial™ intervention and implement it nationwide.…”
Section: Discussionmentioning
confidence: 99%
“…Young and middle-aged adults indicated that they did not grow up with a specific diet and that whole grains were not very popular at the time, also adding that whole grains were not readily available and accepted in the Malaysian population due to their different sensory characteristics when compared to traditional Malaysian cuisines. Increased exposure to an uncommon food has been found in several studies to develop and cultivate a child's liking for that food, and such exposure may even decrease resistance to foods that were previously hated (Koo et al, 2020). Despite a majority of the respondents mentioning that they had previously tried whole grain foods, only a handful of them consumed whole grain foods on a regular basis that indicated habitual intake.…”
Section: Barriers Towards Consumption Of Whole Grain Foodsmentioning
confidence: 99%